Pteridophytes as ecological indicators: an overview - Aline Possamai Della; Daniel de Barcellos Falkenberg (Hoehnea, 2019)
ABSTRACT The pteridophytes present a great but poorly explored potential as ecological indicators (EIs), shown only in some sparse studies. Therefore, to analyze this potential, we reviewed published articles, websites, or books with pteridophytes as EIs, searching on five scholar databases and also on Google. We selected 134 studies, conducted in all continents (118 in mainland areas and 16 in islands). Brazil is the country with the highest number of studies (N = 33). In general, several species were considered as EIs in a given study, not only a single. The use of Pteridophytes in these works was classified in seven different types: a) classification of vegetation, soils, environments, and ecosystems (N = 65), b) environmental integrity (or quality) (N = 21), c) disturbance (N = 17), d) regeneration/restoration of habitats and/or ecosystems (N = 10), e) climate changes (N = 10), f) contamination of air, soil, or water (N = 14), and g) association with other groups of organisms (N = 12). The vast majority of these studies merely hypothesized the potential use of the Pteridophytes as EIs, with few presenting helpful criteria for the selection of EIs. Although there is an increasing recognition of the potential use of Pteridophytes as EIs, a more in-depth discussion about the criteria for selecting Pteridophytes as indicators and the real uses of such plants is needed.